A survey of problems faced by converts to Islam in Malaysia - Sayyid Buhar Musal Kassim; Mohd Syukri Yeoh Abdullah; Zawiyah Baba (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2013)
Islamic conversion is a common daily activity in Malaysia, but there are some problems faced by Muslim converts after their conversion to Islam. These problems could be due to many reasons, such as lack of knowledge, realization, confirmation or confused acceptance of the religion or the sociological complexities or the negative impact of surroundings. Islamic conversion is a voluntary ruhani acceptance of Islamic faith. It could be done at any time by a non-Muslim privately or publically by declaring the kalimah shahadah. However, the issue of conversion is complicated. The transition period experienced by the converts attests their inner conflicts adapting to their new surroundings. Their parental faith may no longer be relevant, but adopting a new religion and living in the same society with different traditions of the old religious faith could lead to traumatic inner conflicts which are invisible. Consequently, these feelings may gradually direct them to various conflicting feelings towards Islam on two continuum; negative insights or otherwise. Research studies have been done about Islamic conversion and its procedures, challenges of Muslim converts, religious authorities and their responsibilities, religious laws and state enactments, about conversion, welfare of Muslim converts and many more. While every convert is different, and his or her experiences differ from person to person, it can be said that majority of converts conform to certain mould. There are identifiable phases which they go through after conversion; elation, emphatic enthusiasm, fanaticism, disillusionment, weakness, and renewal. This survey is to explore certain problems faced by Muslim converts in Malaysia.